Exploring the Experiences of an Elder, a Psychologist and a Psychiatrist: How can Traditional Practices and Healers Complement Existing Practices in Mental Health? - Crowe-Salazar, Noela (First Peoples Child & Family Review, 2007)
This qualitative research study asked the question: how can traditional practices and healers complement existing practices in mental health? Three interviews were conducted with the intention to explore the experiences of people who have expertise in the areas of traditional healing and mental health. Interviews were held with an Elder, a Psychologist and a Psychiatrist. Analysis of the interviews highlighted the different perspectives of each worldview, which is thoroughly discussed in the literature. In addition common themes to practice were identiﬁed and this is an area that is not often highlighted in the literature. The interviews revealed each perspective is strongly grounded in a desire and intention to help people and is then built upon via training. To move forward it is essential to begin from commonalties in how each perspective works to help people, in addition to a solid understanding of the two perspectives and the causes for the current health and mental health of First Nations and Métis.